APPLIKASI BIOCHAR BERBAHAN DASAR LIMBAH KAYU MERANTI (Shorea spp.) UNTUK PERTUMBUHAN MAHONI (Swietenia macrophylla) MENGGUNAKAN MEDIA TAILING EMAS MERANTI (Shorea spp.) BIOCHAR APPLICATION TO MAHONI (Swietenia macrophylla) GROWTH IN GOLD TAILING MEDIA - Maulani, Qori; Riniarti, Melya; Duryat, Duryat; Hidayat, Wahyu (Gorontalo Journal of Forestry Research, 2024)
ABSTRACTTailings are the final result of mining industry activities. Tailings are in the form of sludge waste produced from mining gold, copper, silver and other minerals. Tailings can potentially damage the environment and be dangerous to human life and other creatures. One effort to restore land from tailings is bioremediation technology. Biochar is a soil amendment material that can be used for environmental remediation. Utilizing meranti wood waste as biochar can reduce waste and increase economic value. Mahogany is a type of plant that is known to have potential as a phytoremediation plant. The aim of this research is to determine the effectiveness of meranti wood biochar to improve the growth of mahogany planted in gold tailings media. This research was carried out for four months in a greenhouse. The research was designed using a Completely Randomized Design (CRD) with the treatment of gold tailings and meranti-based biochar in the growing media used. There were 12 treatments with four repetitions. The treatment given is (1) 0% tailings+0% Biochar; (2) 25% tailings+0% biochar; (3) 50% tailings +0% biochar; (4) 0% tailings+5% biochar; (5) 25% tailings + 5% biochar; (6) 50% tailings +5% biochar; (7) 0% tailings + 10% biochar; (8) 25% tailings + 10% biochar; (9) 50% tailings + 10% biochar; (10) 0% tailings + 15% biochar; (11) 25% tailings + 15% biochar; (12) 50% tailings + 15% biochar. The parameters observed were height increase, diameter increase, leaf area and root length. The research results showed that the application of biochar was able to improve the growth of mahogany planted in gold tailings media. Providing 10 and 15% biochar on media with gold tailings even resulted in better mahogany growth compared to those grown on media without tailings. This shows that meranti-based biochar has the ability to become a soil amendment for land contaminated with gold tailings.ABSTRAKTailing merupakan hasil akhir dari kegiatan industri pertambangan. Tailing berbentuk limbah lumpur yang dihasilkan dari pertambangan emas, tembaga, perak maupun mineral lainnya. Tailing dapat berpotensi merusak lingkungan dan berbahaya bagi kehidupan manusia dan makhluk lainnya. Salah satu upaya restorasi lahan dari tailing adalah dengan teknologi bioremediasi. Biochar adalah salah satu bahan pembenah tanah yang dapat digunakan untuk remediasi lingkungan. Pemanfaatan limbah kayu meranti sebagai biochar dapat mengurangi limbah dan meningkatkan nilai ekonomi. Mahoni termasuk tipe tanaman yang diketahui memiliki potensi sebagai tanaman fitoremediasi. Tujuan dari penelitian ini adalah mendapatkan efektifitas biochar kayu meranti untuk memperbaiki pertumbuhan mahoni yang ditanam pada media tailing emas. Penelitian ini dilaksanakan selama empat bulan di rsumah kaca. Penelitian didesign dengan Rancangan Acak Lengkap (RAL) dengan perlakuan pemberian tailing emas dan biochar berbahan dasar meranti pada media tumbuh yang digunakan.  Ada 12 perlakuan dengan ulangan sebanyak empat kali.   Perlakuan yang diberikan adalah (1) 0% tailing+0% Biochar; (2) 25% tailing+0% biochar; (3) 50% tailing +0% biochar; (4) 0% tailing+5% biochar; (5) 25% tailing + 5% biochar; (6) 50% tailing +5% biochar; (7) 0% tailing + 10% biochar; (8) 25% tailing + 10% biochar; (9) 50% tailing + 10% biochar; (10) 0% tailing + 15% biochar; (11) 25% tailing + 15% biochar; (12) 50% tailing + 15% biochar.  Parameter yang diamati adalah pertambahan tinggi, pertambahan diameter, luas daun dan panjang akar.  Hasil penelitian menunjukkan bahwa pemberian biochar mampu memperbaiki pertumbuhan mahoni yang ditanam pada media tailing emas.  Pemberian biochar 10 dan 15% pada media dengan tailing emas bahkan menghasilkan pertumbuhan mahoni yang lebih baik dibandingkan dengan yang ditanam pada media tanpa tailing. Hal ini menunjukkan bahwa biochar berbahan dasar meranti memiliki kemampuan untuk menjadi bahan pembenah tanah bagi lahan lahan tercemar tailing emas.